The Role of Visual Congruence and Self-Expressive Brand in Forming Brand Love That Can Improve E-Wom: A Scientific Investigation Among Sneakers Lovers - Nugroho, Dian Ari (Universitas Ciputra Surabaya, 2023)
Advances in information technology have created a new generation with new and distinct behaviors, particularly in terms of product or service consumption. Social media has evolved into a platform for consumers to share their product-consuming experiences by leaving evaluations based on perceived pleasure. Satisfied customers form attachments and closeness with the brand, resulting in a sense of love for it. Brand love stems from a brand's capacity to represent its customers, and it may also be evident in the visual compatibility between the two parties. Therefore, this study aims to determine the effect of visual congruence, self-expressive brand, on increasing e-WOM mediated by brand love especially among shoes consumers. This explanatory study used respondents from the sneakers-loving population. The purposive sampling technique is used. This research instrument was tested using PLS, validity, reliability, and classical assumption tests. The hypothesis was tested using the t-test. Data analysis technique using Path Analysis. This finding emphasizes the significance of Visual Congruence and Self-Expressive Brand in developing Brand Love and e-WOM, particularly for items that are closely tied to the manner of expression and social behavior of their customers.